HUBUNGAN PENDIDIKAN KESEHATAN DENGAN KECEMASAN ORANG TUA PADA ANAK HOSPITALISASI - Asni Indrayani; Agus Santoso (Jurnal Keperawatan Diponegoro, 2012)
Hospitalization is defined as a process for a reason or an emergency plan that requires the child to stay in the hospital undergoing treatment and care to return back home. During the hospitalization of children, not only the stress experienced by children who are treated but also their parents. Lack of parent knowledge is lead to new stressors in the elderly, which can cause anxiety. The purpose of this study was to determine the relationship between health education and anxiety of parents whose children were hospitalized (hospitalization). This study design is descriptive correlation. Samples were taken by using accidental sampling technique, total of 34 respondents. The results of statistical calculation shows p-value = 0.028. The p-value is < 0.05 indicating a significant relationship between health education and parental anxiety. The study found a significant relationship between health education with parental anxiety, the researchers gave the advice nurse at the hospital in order to provide comprehensive health education to patients and families to cope with anxiety